General view of the city of Vienna - Unknown:::Creator:::::::::::: (Paris; France; Daumont, rue St. Martin)
Color vue d'optique engraving showing a panorama of Vienna, intended for viewing through an optical machine such as a zograscope or peep box with a curved lens and mirror that makes the print appear to be three-dimensional